Hubungan antara Frekuensi Makan dan Kebiasaan Makan dengan Kejadian Stunting di SDN 08 Angata Kabupaten Konawe Selatan - Jaya, Evie Fitrah Pratiwi (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2017)
Nutritional consumption greatly affects the nutritional status of a person's health which is the main capital for individual health. Incorrect or inappropriate nutritional intake will cause health problems. This study was conducted to determine the relationship between eating frequency and eating habits with incidence (stunting) at SDN 08 Angata, South Konawe Regency. This research was conducted with a cross sectional design using a quantitative approach. This research was conducted at the 08 Angata Public Elementary School, South Konawe Regency from 18 May to 02 June 2016. The population in this study were all children who were in the 08 Angata Elementary School, South Konawe Regency, grades 1-5. The sampling method used simple random sampling method as many as 95 children. The independent variables of the study were the frequency of eating and eating habits. The results showed that there was a relationship between the frequency of eating and the incidence of stunting at SDN 08 Angata, South Konawe Regency and there was a relationship between eating habits and the incidence of stunting at SDN 08 Angata, South Konawe Regency. The conclusion that can be drawn is that it is hoped that mothers can pay attention to the type of food consumption in children, especially nutritious food and it is necessary to increase counseling about providing nutritious food for children